Utilization of Mother Child Protection Card (MCP) in Uttar Pradesh, India - Khushbu Arya; Suman Singh (National Geographical Journal of India, 2024)
The Mother and Child Protection (MCP) card is a widely used, user-friendly, community-based tool designed to support an integrated approach to ensuring proper maternity and child care. It promotes survival and growth through family-centered, community-based interventions. This study aims to examine the utilization and distribution of the MCP card in Uttar Pradesh, using data from the fifth round of the National Family Health Survey (NFHS-5) from 2019 to 2021. The primary objective of the present study is to understand the factors influencing MCP card usage. To explore this, bivariate analysis was used to examine the relationships between MCP card utilization and various predictor variables. Additionally, binary logistic regression was employed to determine the overall effect of these predictors on MCP card coverage. The "svyset" command in Stata 17 was used to account for the complex survey design of NFHS-5. Geographic Information System (GIS) mapping using ArcGIS 10.8 was also conducted to visualize distribution patterns. Findings revealed that 95.67% of mothers effectively utilized their MCP cards. Significant variations in MCP card usage were observed based on participants’ backgrounds. Statistical analysis indicated that MCP card utilization was significantly associated with factors such as social group (OR=0.87, CI=0.74–1.02), mothers’ education (OR=1.26, CI=1.05–1.5), religion (OR=0.83, CI=0.7–0.99), and parity (OR=0.86, CI=0.071–1.002). The MCP card provides comprehensive information about maternal and child health services, including background details of both mother and child. Barriers to MCP card access and utilization in Uttar Pradesh range from cultural and social obstacles to illiteracy and lack of awareness.